Silencing a Simple Extracellular Leucine-Rich Repeat Gene OsI-BAK1 Enhances the Resistance of Rice to Brown Planthopper Nilaparvata lugens - Miaofen Ye (MDPI AG, 2021)
Many plant proteins with extracellular leucine-rich repeat (eLRR) domains play an important role in plant immunity. However, the role of one class of eLRR plant proteins—the simple eLRR proteins—in plant defenses against herbivores remains largely unknown. Here, we found that a simple eLRR protein OsI-BAK1 in rice localizes to the plasma membrane. Its expression was induced by mechanical wounding, the infestation of gravid females of brown planthopper (BPH) Nilaparvata lugens or white-backed planthopper Sogatella furcifera and treatment with methyl jasmonate or abscisic acid. Silencing OsI-BAK1 (ir-ibak1) in rice enhanced the BPH-induced transcript levels of three defense-related WRKY genes (OsWRKY24, OsWRKY53 and OsWRKY70) but decreased the induced levels of ethylene. Bioassays revealed that the hatching rate was significantly lower in BPH eggs laid on ir-ibak1 plants than wild-type (WT) plants; moreover, gravid BPH females preferred to oviposit on WT plants over ir-ibak1 plants. The exogenous application of ethephon on ir-ibak1 plants eliminated the BPH oviposition preference between WT and ir-ibak1 plants but had no effect on the hatching rate of BPH eggs. These findings suggest that OsI-BAK1 acts as a negative modulator of defense responses in rice to BPH and that BPH might exploit this modulator for its own benefit.